TEKTUALITAS DAN KONTEKSTUALITAS DALAM PENAFSIRAN DAN PENGARUHNYA BAGI KEHIDUPAN SOSIAL KEMASYARAKATAN (Korelasi Antara Ahlul Bait dan Habaib Ba'alwi, dan Legitimasi Spiritual serta Peran Sosial dalam Penyebaran Islam Nusantara) - Ruhan Basyir, Djazuli (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
The relationship between the ahlul bait-family of the Prophet Muhammad Saw and the habaib (Ba'alwi family) has become an important study in Islamic tradition, especially in the context of their history and social role in the Islamic world. Ahlul bait have a special position in Islam because of their direct lineage to the Prophet Muhammad, as stated in various narrations and interpretations of the Qur'an (Al-Ahzab/33: 33). On the other hand, habaib, especially the Ba'alwi family, is known as one of the branches of ahlul bait which has had a great influence, especially in the spread of Islam in the archipelago. Understanding this correlation is important to examine how their spiritual legitimacy and leadership are built, both in religious and social aspects. Furthermore, this research aims to explain how the values inherited from the ahlul bait are passed on through the habaib tradition and their impact on the development of local Islam. Therefore, it is hoped that this discussion can make a significant contribution to Islamic studies, especially in revealing the dynamic role of spirituality and family traditions in the formation of Muslim identity in the archipelago.